The Promise and The Lost City of Z: Diasporas, Cinematic Imperialism and Commercial Films - Balakian, Sophia; Dominguez, Virginia R. (Anthropologica, 2019)
Through a mutual interview exchange, the authors reflect on two recent commercial films – The Promise and The Lost City of Z. The films deal with the Armenian genocide and British exploration of the Amazon, respectively, both chronicling events that took place in the early twentieth century. The authors’ inquiries address questions of diasporic imperialism through film, Othering, violence, and the US movie industry. While differing in their readings and opinions of the films, the authors argue that both movies reflect contemporary US fantasies and preoccupations, and that commercial cinema – and pop culture in the Global North more broadly – ought to be taken more seriously by anthropologists.